An Exploration and Reclamation in Bio Ecology With Reference To the Works the Language of Plants by Monica Gagliano and the Lorax by Dr. Seuss - E. Anitha Christy, (International Journal of Scientific Research in Science and Technology, 2024)
Monica Gagliano is an Italian plant ecologist and researcher who has made significant contributions to the field of plant neurobiology and ecology. She was born in Italy and grew up in a family of scientists and always had a fascination with the natural world. In “The Language of plants” Gagliano argue that plants are active agents, capable of perceiving responding and adapting to their environment. She explores the various ways plants communicate, including chemical signals, electrical impulses and sound waves. The book emphasizes the importance of understanding plants as integral components of ecosystems.